Weakly ALC-Spaces (WALC-Spaces) - Delfi Ali, Reyadh (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this paper is the study certain operation and properties of weakly as spaces in which every almost Lindelöf subset is closed, we continue the investigation of more relationships.